The role of autologous micrografts injection from the scalp tissue in the treatment of COVID‐19 associated telogen effluvium: Clinical and trichoscopic evaluation. Issue 7 (6th May 2022) - Hawwam, Soha Abdalla; Ismail, Mayada; Elhawary, Esraa E.
Abstract: The clinical presentation of severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2 COVID‐19) varies from asymptomatic infection to a life‐threatening, multiorgan disease. One of these manifestations is telogen effluvium (TE) which is characterized by diffuse hair loss occurring in patients previously infected with SARS‐CoV‐2 and lasts ~3 months, after which excessive hair loss follows. Hair follicles are known to contain a well‐characterized niche for adult stem cells which is the bulge containing epithelial and melanocytic stem cells. Stem cells in the hair bulge, a demarcated structure within the lower permanent portion of hair follicles, can generate the interfollicular epidermis, hair follicle structures, and sebaceous glands. This study aims to evaluate autologous micrografts from scalp tissues as a therapeutic modality in the management of TE caused by COVID‐19. Twenty patients of previous COVID‐19 infection suffered from TE were included in this study for human follicle stem cells micrograft scalp treatment and they were evaluated after 3 months of treatment and after 6 months. There was significant improvement of the hair thickness and density compared with the start of the treatment and 6 months of follow‐up. Autologous micrograft of the scalp showed marked improvement in the treatment of COVID‐19 TE.